1996
DOI: 10.1063/1.472078
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline structures of pristine and hydrated mercaptohexanol self-assembled monolayers on Au(111)

Abstract: Crystalline structures of pristine and hydrated mercaptohexanol selfassembled monolayers on Au (111) The temperature dependence of the atomic composition of the surface of Cu(100) after deposition of submonolayer films of Au AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 20 publications
(17 reference statements)
3
62
0
Order By: Relevance
“…In our previous study of alkanethiols, we found that besides the interaction of the sulfur atoms in the head group with the iron surface, the inter-chain interactions resulting from van der Waals forces and non-bond interactions made a signicant contribution to the stabilization of the adsorbed layers. 22,[27][28][29][30] Also, with the various molecular classes studied here, the geometric factors were also signicant (Table 3). 31 Substantial changes in charge-transfer resistance resulted with the addition of long-chain alkanethiols (dodecanethiol and octanethiol), the aromatic thiols (benzenethiol and 2-methylbenzenethiol), the short-chain dithiol (1,2-diethanethiol) and the small cyclic ether (1,4-dithiane).…”
Section: Impedance Spectroscopy and The Properties Of Adsorbed Layers...mentioning
confidence: 99%
“…In our previous study of alkanethiols, we found that besides the interaction of the sulfur atoms in the head group with the iron surface, the inter-chain interactions resulting from van der Waals forces and non-bond interactions made a signicant contribution to the stabilization of the adsorbed layers. 22,[27][28][29][30] Also, with the various molecular classes studied here, the geometric factors were also signicant (Table 3). 31 Substantial changes in charge-transfer resistance resulted with the addition of long-chain alkanethiols (dodecanethiol and octanethiol), the aromatic thiols (benzenethiol and 2-methylbenzenethiol), the short-chain dithiol (1,2-diethanethiol) and the small cyclic ether (1,4-dithiane).…”
Section: Impedance Spectroscopy and The Properties Of Adsorbed Layers...mentioning
confidence: 99%
“…Because of the trans-conformation of the methylene units along the alkyl chain, each alkanethiol occupies an area of about 24 Å 2 ͑5.6 Å in diameter͒. 27 Since the longest distance across the facet of a benzene ring is about 5.0 Å, we assume that the aromatic rings experience little steric hindrance from neighboring alkanethiol molecules in the SAM, and hence possess a high degree of rotational freedom ͑rotation about ␤͒.…”
Section: B Nexafs Spectroscopymentioning
confidence: 99%
“…11,12 Enhanced lateral chain-chain interaction between aromatic thiol molecules results in formation of highly compact rigid SAMs 13,14 and makes them excellent barriers against metal ion penetration in electrolytic media. 15 Properties of SAMs are often tuned by attaching functional termination groups on the molecular chain such as -SH, 16,17 -OH, 2,18 -COOH, 4,19 -SO 3 H, 20 -CN 20,21 and -NH 2 [22][23][24] for appropriate technical applications. A pyridine moiety as a functional group makes these films interesting for a variety of applications.…”
Section: Introductionmentioning
confidence: 99%